Onkel Bennys billeder - Sverdrup-Jensen, Eva (Rambam. Tidsskrift for jødisk kultur og forskning, 2017)
Uncle Benny’s Paintings Benny Cohn was born in 1896 into a Jewish/Christian family. He always wanted to be a painter and his family supported him. He graduated from the Royal Danish Academy of Fine Arts in 1917. He won a golden medal and a travel stipend in 1919. In 1920, Benny settled down in Paris, well known as a skilled painter – especially for his portraits and landscapes. He became a member of Salon d’ Automne in 1921. Benny spent the summers painting in Denmark, and most of his life he continued to exhibit at Charlottenborg in Copenhagen. The family was separated during the Second World War. Benny, his father and sister went to the USA in 1939; his brother Gerson and his children went to Sweden as refugees. Benny’s mother and another sister stayed in Denmark, where his mother died in 1944. In 1949, Benny decided to finally immigrate to the USA. In the USA, he settled down in Rhode Island and began painting colourful, abstract geometric paintings based on music. A dream he had had for a long time. In the USA, Benny used Benjamin Collin as his artist name. This was not so popular with his Jewish family! After his death in 1980, the family of Benny’s American sister inherited his American paintings; and his brother’s family inherited the Danish part. The paintings have been stored away and moved around for many, many years, but in 2014, Benny’s American niece Vikky Stenstream created an exhibition of his abstract paintings in Florida. At the same time, Benny’s Danish niece Eva Sverdrup-Jensen and grandniece Ditte Cohn started to register and renovate the huge Danish collection Benny had left with his brother when he emigrated for the USA. We hope to bring Uncle Benny’s fantastic collection of paintings to live, so that many people can enjoy and appreciate them!